Dental Anxiety in Children With Autism Spectrum Disorder: Understanding Frequency and Associated Variables - Park, Ye; Guzick, Andrew G.; Schneider, Sophie C.; Fuselier, Madeleine; Wood, Jeffrey J.; Kerns, Connor M.; Kendall, Philip C.; Storch, Eric A. (Frontiers in Psychiatry, 2022)
Dental anxiety seems to be elevated in children with autism spectrum disorder (ASD), and may be associated with feelings of helplessness, loss of control, and sensory overload. Dental anxiety, a primary contributor to dental avoidance, can lead to unwanted long-term oral hygiene consequences. This paper characterizes the frequency and correlates of dental anxiety in children with ASD. Specifically, this study examined associations between child-reported dental anxiety and parent-reported autism symptom severity, anxiety symptom severity, sensory sensitivity, and internalizing/externalizing symptom severity. Participants included 76 cognitively-able children (age in years M = 9.9, SD = 1.8) who took part in a cognitive behavioral therapy study for children with ASD and co-occurring anxiety disorders. Elevated dental anxiety was found in 68% of participants based on a cut-off score from a dental anxiety measure, with fears related to pain being the most commonly endorsed concern; over half of youth endorsed feeling scared about pinching feelings or having a tooth pulled out at the dentist. No significant correlations between dental anxiety and other variables of interest were found, including overall anxiety severity, ASD symptoms, internalizing and externalizing symptoms, and sensory sensitivities. The findings contextualize the frequency of dental anxiety and its relationship to various variables, which may be useful in tailoring existing treatments to reduce dental anxiety in children with ASD.